EVALUASI PROGRAM HOME VISIT SEBAGAI PENGUAT PENDIDIKAN KARAKTER DI SMK YPUI PARUNG - Alifia Prima Dini; Ismah Az Zahroh (Universitas Muhammadiyah Purwokerto, 2023)
This study aims to find out how to evaluate the Home Visit Program as strengthening character education at SMK YPUI Parung. This study uses a qualitative method with the CIPP model. The subjects of this study were taken from Guidance and Counseling coordinators, students, and school principals at SMK YPUI Parung. Data collection techniques using the method of observation, interviews, and documentation. The observation method in this study uses participatory methods. Data analysis using data reduction, data presentation, data conclusion. The results of the research show that: (1) in terms of context, the components are background, specific objectives, and program development (2) in terms of input it is quite good, consisting of program target components, elements involved, and the role of the teacher (3) in terms of process, that of the five components, and only three are of good value. While the other two are less valuable. Components which include materials, methods, obstacles, and how to evaluate the evaluation system to develop character values are quite good. While the program implementation methods and efforts to develop character values are not good (4) in terms of products, both components are quite good. This component consists of program achievements and program evaluation.